2022
DOI: 10.2147/rru.s356738
|View full text |Cite
|
Sign up to set email alerts
|

Pilimiction, a Rare Presentation of Ovarian Teratoma: A Case Report

Abstract: Background Adnexal teratoma involving the urinary bladder is a very rare condition. Presentation is variable ranging from irritative LUTS (lower urinary tract symptoms) to pilimiction or trichiuria (passage of hair in the urine). Case Presentation We report a case of a 42-year-old woman who presented with pilimiction and lower abdominal pain. Contrast-enhanced computed tomography scan (CECT) and cystoscopy were used for the diagnosis. Tumor markers were negative. Right … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…2,4 In extrapulmonary TB, affected areas typically include the bones, pleura, lymph nodes, genitourinary system, peritoneal joints, and meninges. 5,6 Genital TB in men is part of UGTB, contributing to almost 8-15% of all types of TB outside the lungs. 6,7 From various literature sources, it has been found that the average age of patients with UGTB is around 20-40 years old, rarely occurring in children due to a long latent period.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…2,4 In extrapulmonary TB, affected areas typically include the bones, pleura, lymph nodes, genitourinary system, peritoneal joints, and meninges. 5,6 Genital TB in men is part of UGTB, contributing to almost 8-15% of all types of TB outside the lungs. 6,7 From various literature sources, it has been found that the average age of patients with UGTB is around 20-40 years old, rarely occurring in children due to a long latent period.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Genital TB in men is part of UGTB, contributing to almost 8-15% of all types of TB outside the lungs. 6,7 From various literature sources, it has been found that the average age of patients with UGTB is around 20-40 years old, rarely occurring in children due to a long latent period. [8][9][10] The demographic characteristics of the patients in this case report resemble existing literature or studies, being male and aged 31 years old.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations